PENCATATAN PERKAWINAN DALAM KAJIAN TEORI MUSHLAHAH DAN HILAH - Kosim Kosim (IAIN Syekh Nurjati Cirebon, 2021)
AbstractSome Indonesian Muslims still question why marriage must be recorded even though in the terms and pillars of marriage in the fiqh books of munakahat marriage registration is not stated to be included in the terms and pillars of marriage, why in Indonesian the problem of registering the marriage is strengthened by legitimacy through Law No. 1 of 1975, strengthened in KHI and PMA No. 11 of 2007 and PMA number 19 of 2018. Marriage registration in Indonesia, although its legitimacy in the Republic of Indonesia is strong, there are still some Muslims in marriage who do not carry out proper marriage registration. already popular in Indonesian society as Siri marriage. In the problem mentioned above, researchers using qualitative methods want to analyze the problem related to why some people are still not sure about the benefits of marriage registration and what is the purpose of the government making law number 1 of 1974, Islamic religious leaders make KHI book 1 about Marriage and the Minister of Religion made regulations Number 11 of 2007 and PMA number 19 of 2018 to legalize marriage records using the analysis of maslahah and hilah theories. The results of the study show that Marriage Recording in the Study of Mashlahah and Hilah Theory is a must because the goal is to maintain the goals of syara' which is framed in five cases, namely maintaining religion, soul, mind, lineage, and property and eliminating evil.